1997
DOI: 10.1021/ja971259t
|View full text |Cite
|
Sign up to set email alerts
|

The Stereochemical Assignment and Conformational Analysis of the V/W-Ring Juncture of Maitotoxin

Abstract: The unambiguous stereochemical assignment of the V/W-ring juncture of maitotoxin, as shown in Figure , was accomplished using a two-step approach:  (1) the synthesis of two diastereomeric models Me-A and Me-B and (2) the comparison of the NMR spectroscopic data for each model with those of maitotoxin. Furthermore, the fact that the NMR characteristics observed for Me-A were remarkably close to those reported for maitotoxin makes a strong case for the accurate extrapolation of the conformational properties of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 25 publications
(24 reference statements)
1
25
0
2
Order By: Relevance
“…Confirmation of the relative configuration of the C99-C100 junction of maitotoxin (13; Kishi and co-workers, 1996). [124] the maitotoxin structure. The first one was specifically developed to take advantage of the acyl furans 417 readily accessible from substituted furans (415) through metalation followed by acylation with 416 (Scheme 71).…”
Section: Maitotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation of the relative configuration of the C99-C100 junction of maitotoxin (13; Kishi and co-workers, 1996). [124] the maitotoxin structure. The first one was specifically developed to take advantage of the acyl furans 417 readily accessible from substituted furans (415) through metalation followed by acylation with 416 (Scheme 71).…”
Section: Maitotoxinmentioning
confidence: 99%
“…To confirm Yasumotos assignment, Kishi and co-workers synthesized the two possible C99-C100 diastereomers (Scheme 68). [124] Thus, starting with enantiopure WX fragment 406 and racemic U fragment 407, they constructed two diastereomers of 408, and then forged ring V through a reductive cyclization of a hydroxy ketone to afford their two targeted diastereomers of 409. Upon separation of the two diastereomers, and comparison of their 13 C chemical shifts with those of the corresponding domain of maitotoxin, they concluded that, indeed, the originally assigned stereochemistry by Yasumoto and coworkers [119] around the VW rings was most likely correct.…”
Section: Maitotoxinmentioning
confidence: 99%
“…Thus, both of them were synthesized, and comparing each one with MTX in 13 C chemical shifts led to the unambiguous assignments of stereochemistry for C5, C7, C8, C9, C12, C13, and C14. 11,12 The configuration of the other acyclic parts, including the absolute stereochemistry of the whole molecule, was determined in a similar manner independently by Kishi's [13][14][15] (4) constructed by NOEs and spin coupling constants (see Section 3.2), one possible conformation was deduced as depicted in Fig. 3, where the hydrophobic polyether chain is long enough to span a lipid bilayer membrane and the hydrophilic portion shows more flexible orientation.…”
Section: Structure and Mode Of Action Of Maitotoxinmentioning
confidence: 99%
“…3 Hierarchical order of intricacy associated with the structural analysis of materials, in terms of polydispersity and molecular heterogeneity (see the main text). The structures (connectivities and stereochemistry) of monodisperse molecules are readily accessible (provided that sufficient amounts of the material are available) by organic structural spectroscopy [ 7 9 ]. Supramolecular structures [ 10 – 12 ] require an adequate definition of the covalently bonded molecules and of their noncovalent interactions [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%